PENGARUH PEMBERIAN TEHNIK RELAKSASI NAFAS DALAM TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN POST OPERASI APPENDIKTOMI HARI PERTAMA DI RUANG BEDAH BLUD RSU DR.M.M DUNDA LIMBOTO KABUPATEN GORONTALO TAHUN 2013 - Pipin Yunus (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Appendicitis is an inflammation due to infection of the appendix or the appendix (appendix). This infection can lead to pus. When the infection gets worse, the appendix can rupture. Appendix is an intestinal tract clogged edges and protruding from the early part of the colon or cecum (cecum). On the surgical treatment of appendicitis. Complaints and symptoms that are often raised include surgical wound pain that is felt is often dealt with the pharmacology of anesthetic or analgesic drugs to suppress pain. The purpose of this study was to determine the Effect of Relaxation Breathing Techniques To Decrease Pain Intensity in Patients Post Operation Appendiktomi In First Day In Space Blud Surgical Hospitals Dr.MM Dunda Limboto. The study design used is descriptive research quasi-experimental design (Quasi-experimental) with one-group pretest-posttest design, the test in the absence of a comparison group (control). Population and sample are all postoperative patients Appendiktomi First Day In Space Blud Surgical Hospitals Dr.MM Dunda Limboto the 15 patients with a total sample of 15 patients. Sampling technique with consecutive sampling technique. Analysis carried out in stages (1) Univariate analysis using frequency distributions. (2) Analysis of the relationship between variables Bivariat for using statistical analysis test chi-square test, in order to determine the relationship of the study variables with a significance value (p value) <0.05 or (5%). Test using the test statistic T dependent reportedly seen the mean difference between the measurements before and after standr deviation is 0.60 and 0.632. P values obtained value is equal to 0.0003 because of p <0.05 No Effect of the Relaxation Breathing Techniques To Decrease Pain Intensity in Patients Post Operation Appendiktomi In First Day In Space Blud Surgical Hospitals Dr.MM Dunda Limboto